The influence of the family structure on the academic performance of secondary pupils in the Maseru region - Letsie, Puleng Relebohile (University of the Free State, 1998)
This study investigated the influence of the family structure on the academic performance of secondary school pupils in the Maseru region. It should be realised that this is a very controversial issue according to the researcher as some people in the community strongly believe that children from single-parent families do not perform well academically, while others object to it strongly. At the same time, it cannot be denied that the family structure can have a great influence on the academic performance of pupils. The attitudes and opinions of pupils towards the effect of the family structure on academic performance were investigated on a theoretical and empirical basis. In this study the researcher defined various relevant concepts used in the study. The theoretical framework related to family structures and academic performance, is divided in four chapters. The first chapter is the general orientation of the study, that is, the problem is stated, the necessity of the study explained, the aim of the research, research questions, definition of terms, demarcation of the research area, method of investigation and the course of study have been elaborated in the first chapter. The second chapter deals with different family structures, with sub-topics such as historical family structures, types of family structures, changes in family structures and the results of a change in the family structure. The third chapter mainly deals with adolescence and family structures. Included in this chapter are concepts such as the nature of adolescence, the adolescent's family and family relationships and adolescent development. The fourth chapter, being the last theoretical chapter, deals with factors influencing the adolescent's intellectual development and academic performance. Issues discussed in this chapter are intelligence and intellectual growth, academic performance and achievement, main factors affecting adolescents' intelligence and academic achievement and the changes in family structures and their effects on performance. For the empirical research, the researcher firstly outlaid the practical steps and activities aimed at gathering information from pupils by means of questionnaires. Finally, the researcher tabulated the results from all respondents. The data was analysed and processed by means of the programme called the Statistical Package for Social Sciences (SPSS). Findings were discussed in relation to the tables according to various responses from the respondents, and then analysed. On the basis of the theoretical findings, the researcher came to the conclusion that the family structure does not have much influence, if any, on the academic performance of secondary pupils. In the empirical study on the other hand, the family structure clearly affects pupils' academic performance. Recommendations made by the researcher are based chiefly on the findings of the empirical study.

In hierdie studie word die invloed van die gesinstruktuur op die akademiese prestasie van sekondêre leerlinge in die Maseru-omgewing ondersoek. Volgens die navorser is hierdie 'n baie kontroversiële aangeleentheid omdat sommige mense in die gemeenskap sterk daaraan glo dat kinders van enkel-ouergesinne akademies nie goed presteer nie, terwyl ander weer dié siening sterk teenstaan. Hoe dit ookal sy, dit kan nie ontken word nie dat die gesinstruktuur wel 'n groot invloed uitoefen op die akademiese prestasie van leerlinge. Die houdings en opvattings van leerlinge betreffende die effek van die gesinstruktuur op akademiese prestasie was teoreties sowel as empiries ondersoek. In die studie het die navorser verskeie relevante konsepte wat in die ondersoek ter sprake was, gedefinieer. Die teoretiese raamwerk wat oor die gesinstruktuur en akademiese prestasie gehandel het, is 'in vier hoofstukke verdeel. Die eerste hoofstuk is die algemene oriëntasie van die ondersoek: die uiteensettting van die probleem, verduideliking van die noodsaaklikheid van die ondersoek en die doel van die studie, die formulering van navorsingsvrae, definiëring van terme, afbakening van die veld en metode van ondersoek en aanduiding van die verdere verloop van die studie. Die tweede hoofstuk handelaar verskillende moontlike gesinstrukture, met subhoofde soos die historiese agtergrond van verskillende gesinstrukture, tipes gesinstrukture, veranderinge in die gesinstruktuur en die uitwerking van sodaninge veranderinge. In hoofstuk drie word hoofsaaklik aandag gegee aan die adolessent en die gesinstruktuur. In hierdie hoofstuk word konsepte hanteer soos die aard van adolessensie, die adolessent se gesin en sy/haar gesinsverhoudinge en ontwikkeling. Die vierde hoofstuk handel weer oor faktore wat die adolessent se intellektuele ontwikkeling en akademiese prestasie beïnvloed. Aspekte wat in dié hoofstuk bespreek word, is intelligensie en intellektuele groei, akademiese prestasie, belangrikste fak tore wat die adolessent se intelligensie affekteer en die veranderinge in die gesinstruktuur en die effek daarvan op syjhaar prestasie. Vir die empiriese ondersoek het die navorser eerstens die praktiese stappe uiteengesit wat aangewend is om inligting van die leerlinge te bekom deur middel van vraelyste. Aan die einde is die resultate van al die respondente in tabelvorm weergegee. Die data was geanaliseer en geprosesseer deur middel van die Statistiese Program vir Sosiale Wetenskappe (SPSS). Bevindinge was aan die hand van die tabelle uiteengesit en geanaliseer. Teoretiese bevindinge het daarop gedui dat die gesinstrutuur nie noemenswaardige invloed uitoefen op die akademiese prestasie van die sekondêre leerlinge nie. Die navorser se empiriese ondersoek het, aan die ander kant, weer laat blyk dat die gesinstruktuur duidelike effek het op hulle akademiese prestasie. Die navorser se aanbevelings is hoofstaaklik gebasseer op die empiriese bevindinge in die ondersoek.
Dissertation (M.Ed. (Psychology of Education))--University of the Free State, 1998
Keywords: Academic achievement -- Lesotho -- Maseru -- Testing; Children -- Family relationships; High school students -- Education -- Lesotho -- Maseru